Penyuluhan tentang Pemantauan Tumbuh Kembang dan Pemberian Vitamin A pada Balita di Posyandu Kenanga Desa Mampir Kec. Cileungsi Kabupaten Bogor Tahun 2021 - Yulita Nengsih; Imelda Diana Marsilia (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
The quality of a child can be judged from the process of growth and development. The process of growth and development is the result of the interaction of genetic factors and environmental factors. Genetic/hereditary factors are factors related to genes originating from the father and mother, while environmental factors include the biological, physical, psychological, and social environment. Growth and development have increased rapidly at an early age, from 0 to 5 years. This period is often referred to as the